Correction: Fabrication of red blood cell membrane-camouflaged Cu2−xSe nanoparticles for phototherapy in the second near-infrared window. Issue 25 (18th March 2020) - Liu, Zhou; Wang, Jinquan; Qiu, Kangqiang; Liao, Xinxing; Rees, Thomas W.; Ji, Liangnian; Chao, Hui
Abstract : Correction for 'Fabrication of red blood cell membrane-camouflaged Cu2− x Se nanoparticles for phototherapy in the second near-infrared window' by Zhou Liu et al., Chem. Commun., 2019, 55, 6523–6526.